High pathogenicity of a Chinese NADC34-like PRRSV on pigs - Yuan, L.; Zhu, Z.; Fan, J.; Liu, P.; Li, Y.; Li, Q.; Sun, Z.; Yu, X.; Hu Suk Lee; Tian, K.; Li, X. (American Society for Microbiology, 2022)
NADC34-like porcine reproductive and respiratory syndrome virus (PRRSV) has been reported to be prevalent in China since 2018 and became one of the main epidemic strains in some areas of China. Yet, the pathogenicity of NADC34-like PRRSV tested by experimental infection has seldomly been investigated. In this study, we infected pigs with JS2021NADC34 PRRSV, a Chinese NADC34-like PRRSV isolated in Jiangsu province in 2021, to study the pathogenicity of this virus strain. Pigs infected with this virus had lasting fever and reduced body weight with high morbidity and mortality. Histopathological changes, including interstitial pneumonia, lymphocyte depletion, acute hemorrhage, and infiltration of neutrophils in the lymphoid tissues, were observed with the viral proteins detected by immunohistochemistry staining using PRRSV-specific antibody. These results suggested that JS2021NADC34 PRRSV is highly pathogenic to pigs. As it is the latest emerging PRRSV strain in China, the prevalence and pathogenicity of NADC34-like PRRSV need to be further investigated.